2011
DOI: 10.1007/s10096-011-1410-z
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of IncA/C conjugative plasmid harboring bla TEM-52 and bla CTX-M-15 extended-spectrum β-lactamases in clinical isolates of Escherichia coli in Tunisia

Abstract: To characterize the extended-spectrum β-lactamases (ESBLs) as well as their genetic environment in different isolates of Escherichia coli from patients with repeated urinary tract infections, large multidrug resistance (MDR) plasmids have been found. Definitive evidence for the presence of an A/C incompatibility complex (IncA/C) plasmid in the MDR isolates was provided by the probing of plasmids extracted from the clinical isolates. Conjugation experiments showed that bla genes were transferred by conjugation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…In this study, three bla OXA-48- containing plasmids also harboured bla CTX-M genes and belonged to the IncA/C group. Although most bla CTX-M-15 were associated with the IncFIIA plasmid, the IncA/C plasmid has also been shown to be related with bla CTX- M, and presumably the dissemination of CTX-M enzymes [ 17 , 18 ]. Unlike the epidemic bla OXA-48 plasmid incompatibility type, IncL/M [ 19 ], this is the second study to identify bla OXA-48 on an IncA/C plasmid [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, three bla OXA-48- containing plasmids also harboured bla CTX-M genes and belonged to the IncA/C group. Although most bla CTX-M-15 were associated with the IncFIIA plasmid, the IncA/C plasmid has also been shown to be related with bla CTX- M, and presumably the dissemination of CTX-M enzymes [ 17 , 18 ]. Unlike the epidemic bla OXA-48 plasmid incompatibility type, IncL/M [ 19 ], this is the second study to identify bla OXA-48 on an IncA/C plasmid [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, owing to many financial limitations, we were unable to sequence these genes. However, it is worthy of note that in Tunisia bla CTX-M-1 and bla CTX-M-15 are predominant in enterobacteria isolates, especially in E. coli, from animal and human origins, respectively [Chouchani et al, 2012;Kilani et al, 2015]. Therefore, it is likely that most bla CTX-M genes found in our isolates might be of bla CTX-M-1 type.…”
Section: Discussionmentioning
confidence: 80%
“… 32 The presence of the insertion sequence IS Ecp1 upstream from the bla CTX-M genes was determined by PCR and sequencing as previously described. 11 Sequencing of the genes was performed by the Macrogen ® DNA Sequencing Service (Macrogen, Amsterdam, the Netherlands) using sets of consecutive primers specific for each gene type.…”
Section: Methodsmentioning
confidence: 99%
“… 10 It has been reported that the bla CTX-M-15 gene is usually found downstream from the insertion sequence IS Ecp1 that may be involved in their dissemination and expression. 11 Plasmid-mediated ESBL genes are of special interest due to their capability of getting transferred between strains or even species, favoring their dissemination among the bacterial population and from region to region. Moreover, these plasmids usually carry other antibiotic resistance determinants, resulting not only in the spread of ESBL but also in the dissemination of other resistance genes.…”
Section: Introductionmentioning
confidence: 99%